Deep Learning With EEG Spectrograms in Rapid Eye Movement Behavior Disorder - Ruffini, Giulio; Ibañez, David; Castellano, Marta; Dubreuil-Vall, Laura; Soria-Frisch, Aureli; Postuma, Ron; Gagnon, Jean-François; Montplaisir, Jacques (Frontiers in Neurology, 2019)
REM Behavior Disorder (RBD) is now recognized as the prodromal stage of α-synucleinopathies such as Parkinson's disease (PD). In this paper, we describe deep learning models for diagnosis/prognosis derived from a few minutes of eyes-closed resting electroencephalography data (EEG) collected at baseline from idiopathic RBD patients (n=121) and healthy controls (HC